OPTIMIZING OPERATING PARAMETERS AND POLYACRYLIC ACID ANTISCALANT DOSAGE IN A REVERSE OSMOSIS UNIT - M Khoirul Ummam; Irfan Purnawan; Nurul Hidayati Fithriyah (Journal of Applied Sciences and Advanced Technology, 2025)
Reverse osmosis (RO) technology is one of the most widely used and highly effective filtration technologies. RO membranes generally act as barriers to dissolved salts and inorganic compounds, as well as organic molecules witmolecular weights greater than 100 angstroms. Several factors influence the rate of mineral scale formation on the surface of RO membranes, including lower temperatures, which reduce mineral scale solubility, and higher feedwater conductivity or Total Dissolved Solids (TDS), which increase the solubility of slightly soluble salts. This phenomenon is caused by increased ionic interference during the nucleation and crystallization processes of various types of scale. Mineral scaling remains a critical challenge in reverse osmosis (RO) systems, limiting recovery and increasing operational costs. This study optimizes polyacrylic acid (PAA) antiscalant dosage and system recovery in a 120 m³/h industrial BWRO (brackish water reverse osmosis) plant treating water with 20–40 ppm Ca-hardness. Dosages of 3–13 ppm and recoveries of 49–75% were evaluated based on normalized permeate flow (NPF) decline and feed pressure increase, targeting <10% performance loss. Results show that a dosage of 11–13 ppm at 74–75% recovery maintains membrane performance with less than 6.5% NPF decline and minimal pressure increase (below 1.64%) over a production volume of 6,500 m3. Statistical validation (R² > 0.96, p < 0.05) confirms the significance of these parameters, while Hyd-RO-Dose simulations support calcite saturation control. These findings provide a practical, validated framework for optimizing RO operation by enhancing efficiency and reducing fouling, as well as antiscalant dosing in industrial settings.